Our Experience with Percutaneous and Surgical Tracheotomy in Intubated Critically Ill Patients - Ülkümen, Burak (Turk Arch Otorhinolaryngol, 2018)
OBJECTIVE: Open surgical tracheotomy (OST) and percutaneous dilatational tracheotomy (PDT) are commonly used for securing airway in intubated critically ill patients. The purpose of this study was to compare the safety of OST and PDT, particularly in intubated critically ill patients. METHODS: The medical records of intubated critically ill patients who underwent tracheotomy between August 2006 and July 2017 were analyzed retrospectively. Minor and major complication rates were compared according to the tracheotomy technique. Preoperative intubation time, postoperative decannulation time, reason for hospitalization, and demographic data, including the Acute Physiology and Chronic Health Evaluation (APACHE II) and Sequential Organ Failure Assessment (SOFA) scores, were evaluated. RESULTS: A total of 332 cases were enrolled into the study. The minor and major complication rates for both techniques were 27.2%, 8.8%, 9.7% and 3.2%, respectively. Minor and major complication rates were higher in the OST group (p=0.01, p=0.03, respectively). The rate of every single complication was also compared on groups’ basis. Accidental decannulation (p=0.02) and pneumothorax (p=0.05) were found to be significantly frequent in the OST group. There was no impact of the preoperative intubation time on the minor (p=0.20) and major complication (p=0.29) rates found. There was no statistically significant difference regarding the postoperative decannulation time (p=0.32). Also, there was no statistically significant difference between two groups in terms of the APACHE II (p=0.69) and SOFA (p=0.37) scores. However, a statistically significant difference between the groups in terms of overall survival was found, in favor of PDT (p<0.001). CONCLUSION: This study revealed that PDT is safer than OST, particularly in intubated critically ill patients.